The impact of simulation sequencing on perceived clinical decision making. (September 2017) - Woda, Aimee; Hansen, Jamie; Paquette, Mary; Topp, Robert
Abstract: An emerging nursing education trend is to utilize simulated learning experiences as a means to optimize competency and decision making skills. The purpose of this study was to examine differences in students' perception of clinical decision making and clinical decision making-related self-confidence and anxiety based on the sequence (order) in which they participated in a block of simulated versus hospital-based learning experiences. A quasi-experimental crossover design was used. Between and within group differences were found relative to self-confidence with the decision making process. When comparing groups, at baseline the simulation followed by hospital group had significantly higher self-confidence scores, however, at 14-weeks both groups were not significantly different. Significant within group differences were found in the simulation followed by hospital group only, demonstrating a significant decrease in clinical decision making related anxiety across the semester. Finally, there were no significant difference in; perceived clinical decision making within or between the groups at the two measurement points. Preliminary findings suggest that simulated learning experiences can be offered with alternating sequences without impacting the process, anxiety or confidence with clinical decision making. This study provides beginning evidence to guide curriculum development and allow flexibility based on student needs and available resources. Highlights: Sequencing of simulated learning experiences did not impact clinical decision making. Anxiety was significantly decreased in students who had simulated learning experiences first. Simulated learning experiences prior to caring for patients may decrease anxiety. Students who had simulated learning experiences first had higher levels of self-confidence. Research is needed to determine the optimal integration of simulated learning experiences.